Motivación académica en estudiantes de vinculación a la sociedad de las carreras de Psicopedagogía y Educación Inicial de la Unach - Aguirre Sánchez, María José (2024)
The purpose of this research was to determine the level of academic motivation of the students, who make links to society, of the careers of Psychopedagogy and Early Education of the National University of Chimborazo, a sample of 91 students was worked on; 53 from the Psychopedagogy career and 38 from the Initial Education career of the UNACH. The research approach was quantitative and descriptive-cross-sectional. Data collection was carried out through the Motivational and Learning Strategies MLSQ questionnaire consisting of 81 items distributed in two scales: Motivation and Learning Strategies, working in this research only with the motivation scale, the results obtained were the following: within the extrinsic and intrinsic orientation, the level was medium for both students of the Psychopedagogy career and the Early Education career and with a minimal difference in the level.